Digital Transformation in Public Administration in Vietnam: Current Status, Challenges, and Policy Implications - Thi Thanh Mai, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
Public-sector digital transformation is shifting from merely “putting forms online” to a data- and platform-based digital government model (digital-by-design/GaaP). Vietnam has embedded this direction into administrative reform, yet gaps remain between central and local levels. The objective of this article is to i) Systematize relevant theoretical and policy foundations; ii) Assess the current situation using the synthesized COAO framework (Capabilities-Operations-Adoption-Outcomes); and iii) Suggest action priorities to increase the use of online public services and maximize public value. The study finds clear progress in the legal framework, digital identification (eID/VNeID), data-sharing platforms (NDXP, national databases), redesign of “one-stop shop” processes with SLAs and real-time tracking, and expanded connectivity infrastructure. However, the uptake of online public services remains low and uneven across localities; mobile/UX experience is still weak; interoperability, data standards, and contextual metadata are not yet unified; and personal-data protection is inconsistent, affecting trust. Based on this, the paper proposes five directions: mobile-first service design; “clean-standard-open” data with common APIs/metadata; deep BPR to make transactions digital-by-default; privacy-by-design; and measurement-disclosure-accountability mechanisms, implemented in 12-18-month rolling waves for high-frequency procedures.